-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathbuilding.tex
643 lines (563 loc) · 32 KB
/
building.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
515
516
517
518
519
520
521
522
523
524
525
526
527
528
529
530
531
532
533
534
535
536
537
538
539
540
541
542
543
544
545
546
547
548
549
550
551
552
553
554
555
556
557
558
559
560
561
562
563
564
565
566
567
568
569
570
571
572
573
574
575
576
577
578
579
580
581
582
583
584
585
586
587
588
589
590
591
592
593
594
595
596
597
598
599
600
601
602
603
604
605
606
607
608
609
610
611
612
613
614
615
616
617
618
619
620
621
622
623
624
625
626
627
628
629
630
631
632
633
634
635
636
637
638
639
640
641
\chapter{New Proofs from Old} \label{new}
As the old saying goes, ``don't work harder, work smarter.'' You've
done the hard work writing a lot of proofs; now it's time to work
smarter. In this chapter, we're going to think about how you can
reliably take short-cuts with proofs. The key word here is
``reliably.'' That is, we want to ensure that these shortcuts won't
cause you to misjudge whether or not something can be proven.
For example, suppose that we ask you to prove the sequent:
$\vdash (P\to Q)\vee \neg (P\to Q)$. You've probably never proved this
sequent before. However, you should have -- if you've been diligent
-- proved an instance of the law of excluded middle, i.e.\ something
like $\vdash P\vee \neg P$. Now suppose that you have the proof of
$P\vee\neg P$ saved in a file \texttt{em.txt}, and that you run a
``find and replace'' to swap in $P\to Q$ for $P$. Then, the result
will be a proof of $(P\to Q)\vee \neg (P\to Q)$. That's working
smart: take an old proof, run find-and-replace, and ta da, you have a
new proof.
What we just did was a case of {\it substitution}. We'll discuss
substitution in the first section. Then we'll talk about another
short-cut method that allows you to splice an old proof into a new one
--- the method of {\it cut}. Finally, we'll talk about a third
short-cut method that allows you to {\it replace} a sub-formula with
any logically equivalent sub-formula. If you learn these three
methods, you'll be able to prove even the most challenging
propositional logic sequents with ease.
\section{Substitution}
In this section, we describe the theoretical basis for the
``find-and-replace'' method of generating new proofs from old. To
this end, we first need to define the notion of a
\emph{\gls{substitution instance}}. \index{substitution instance} The
idea here is that the find-and-replace operation changes a formula
$\phi$ to a substitution instance $\phi ^*$, and a proof of
$\phi\vdash\psi$ to a proof of $\phi ^*\vdash\psi ^*$.
Each sentence of our symbolic language is either one of the symbols
$P,Q,R,\dots $, or it's built up from those symbols using the
connectives $\neg,\wedge ,\vee$ and $\to$. It's time to be a bit more
precise about the ways in which we permit sentences to be constructed.
We call the capital letters $P,Q,R\dots $ our \emph{\glspl{atomic
sentence}}, the idea being that they have no internal structure.
\index{sentence!atomic} We also stipulate that if $\phi$ and $\psi$
are sentences, then $\neg\phi$, $\phi\wedge\psi$, $\phi\vee\psi$, and
$\phi\to\psi$ are also sentences. (To be even more precise, we have
to put parentheses around the resulting sentence at each stage of
construction. However, we will omit parentheses after applying
$\neg$, and we will omit the outermost parentheses from every
sentence.) What's more, we stipulate that all legitimate sentences
come about from applying a finite number of these construction steps.
We now define a notion of a
\emph{\gls{translation}}. \index{translation} For simplicity, let's
suppose that we begin with a list $P,Q,R,\dots $ of simple sentences.
A \emph{\gls{reconstrual}} \index{reconstrual} is an assignment $F$ of
each atomic sentence $X$ to some other sentence $F(X)$. For example,
$F(P)$ could be another atomic sentence, such as $R$, or it could be a
complex sentence such as $R\to \neg S$, or even $\neg P$ or
$P\wedge\neg P$. There are no restrictions at all on the assignment
$F$, so long as the result is a legitimate sentence.
Once we have a reconstrual $F$, we can use it to translate {\it any}
sentence $\phi$. In short, we define $F(\phi )$ to be the sentence
that results from replacing each atomic sentence $X$ in $\phi$ with
$F(X)$. The resulting string of symbols $F(\phi )$ will always be a
legitimate sentence, and we call it a substitution instance of $\phi$.
As usual, the definition becomes more clear when we look at examples.
Suppose, for example, that we reconstrue $P$ as $Q\to P$, and $Q$ as
$\neg R$. That reconstrual results in the following substitution instances.
\[ \begin{array}{l l l}
P\to Q & \leadsto & (Q\to P)\to \neg R \\
P\vee \neg P & \leadsto & (Q\to P)\vee \neg (Q\to P) \\
Q\to P & \leadsto & \neg R \to (Q\to P) \end{array} \] It should
be clear that there is some sense in which the substitution operation
preserves the form of the original sentence; or, to be more precise,
that $F(\phi )$ is an instance of the form presented by $\phi$.
However, $F(\phi )$ can have more structure than $\phi$ itself has;
for example, {\it every} sentence is a substitution instance of the
atomic sentence $P$.
%% exercise
\begin{exercise} Which of the following formulas is a substitution instance of
the formula $P\to \neg Q$? In cases where you answer affirmatively,
show how to reconstrue $P$ and $Q$ to get the resulting formula.
\begin{enumerate}
\item $\neg Q\to \neg P$
\item $(P\to \neg Q)\to R$
\item $(P\to \neg Q)\to \neg (P\to \neg Q)$.
\end{enumerate}
\end{exercise}
Recall that our inference rules are schematic, i.e.\ they depend only
on the form of the sentences involved. Thus, it should immediately
follow that substitution preserves validity, since it preserves form.
We will prove that rigorously in Chapter \ref{meta}, with a result
known as the \emph{substitution theorem}. But for now, it will
suffice to state the upshot, which we can use to generate new proofs
from old ones.
\bigskip
\begin{tcolorbox}[enhanced,width=10cm,title=substitution,attach boxed title to top
left={yshift=-2mm,xshift=4mm},boxed title style={sharp corners}]
A proof of $\phi _1,\dots ,\phi _n\vdash\psi$ can be converted to a
proof of $F(\phi _1),\dots ,F(\phi _n)\vdash F(\psi )$, where $F$ is
a reconstrual of the non-logical vocabulary.
\end{tcolorbox}
\bigskip
The \emph{substitution meta-rule} is just a formalization of what you
already know: that find-and-replace preserves the validity of proofs
(as long as you restrict the finding to atomic sentences, and you
replace them with other well-formed sentences). Note that
substitution is not a rule in the same sense as, say, modus ponens,
which generates new valid inferences. To illustrate this point,
imagine that proofs of all valid sequents are saved in some computer
file $\mathsf{proofs.txt}$. Each such proof consists of finitely many
lines, and in the right hand column, every line is justified by one of
the inference rules: $\wedge I$, $\wedge E$, MP, etc. None of those
lines is justified by some rule called ``substitution.'' Instead, the
substitution meta-rule tells us that for any proof in
$\mathsf{proofs.txt}$, there is another proof in $\mathsf{proofs.txt}$
that looks just like the first, except that the atomic sentences have
been replaced by some other sentences.
\begin{exercise} Do you think the following claims are true or false?
Explain your answers.
\begin{enumerate}
\item If $\phi$ is not provable, then no substitution instance of
$\phi$ is provable.
\item The sentence $(P\wedge Q)\to R$ has a substitution instance
that can be proven.
%% For each sentence $\psi$, if $\psi$ doesn't imply $\bot$, then
%% there is an elementary conjunction $\phi$ such that
%% $\phi\vdash\psi$.
\end{enumerate} \end{exercise}
\section{Cut}
We now introduce a key meta-rule that, if used correctly, can greatly
increase your efficiency in proving things. Let's begin with an
example.
Suppose that you've been asked to prove that
\[ P\to (Q\vee R)\:\vdash\: (P\to Q)\vee (P\to R) .\] After many
failed attempts, you might decide to bring out the sledgehammer of
reductio ad absurdum: to assume the negation of the result you want,
and derive a contradiction. Now, the negation
$\neg ((P\to Q)\vee (P\to R))$ doesn't look to be all that useful.
However, you might then remember that you've already proven the
following version of DeMorgan's rule:
$\neg (P\vee Q)\vdash \neg P\wedge \neg Q$. You could then substitute
$P\to Q$ for $P$, and $P\to R$ for $Q$, which gives you a proof of
\[ \neg ((P\to Q)\vee (P\to R)) \: \vdash \: \neg (P\to Q)\wedge \neg
(P\to R) .\] But now you've got to figure out how to splice that
proof into the proof you're currently working on. The cut meta-rule
will allow you to perform this splice, yielding the following lines:
\[ \begin{array}{l l >{$}p{4.5cm}<{$} p{3cm}}
1 & (1) & P\to (Q\vee R) & A \\
2 & (2) & \neg ((P\to Q)\vee (P\to R)) & A \\
2 & (3) & \neg (P\to Q)\wedge \neg (P\to R) & cut,
DM \end{array} \]
The basic idea here is that if you've proven a sequent
$\phi\vdash\psi$ (such as DeMorgan's), then you can use that sequent
to continue a proof from a line with $\Gamma\vdash\phi$ to a line with
$\Gamma\vdash\psi$. We state the rule, however, in a more general fashion.
\bigskip \begin{tcolorbox}[enhanced,width=10cm,title=cut,attach boxed
title to top left={yshift=-2mm,xshift=4mm},boxed title style={sharp
corners}]
Suppose that you have already demonstrated that \newline
$\phi _1,\dots ,\phi _n\vdash\psi$. Then in any proof where you
have lines $\Gamma _1\vdash\phi _1,\dots ,\Gamma _n\vdash\phi _n$,
you may infer that $\Gamma _1,\dots ,\Gamma _n\vdash \psi$.
\end{tcolorbox}
%% justification
\bigskip As with substitution, cut is not a new inference a new rule.
Instead, it's a promise: if certain proofs exist, then so does another
proof. Imagine again a computer file $\mathsf{proofs.txt}$ that
contains all correctly written proofs. The word ``cut'' does not
appear in any of those proofs. However, if $\mathsf{proofs.txt}$
contains proofs of $\phi _1,\dots ,\phi _n\vdash\psi$, and also of
each $\Gamma _i\vdash\phi _i$, then cut promises that
$\mathsf{proofs.txt}$ also has a proof of
$\Gamma _1,\dots ,\Gamma _n\vdash\psi$. That latter proof, however,
only cites the primitive inference rules such as $\wedge I$ and $MP$.
When you write proofs, however, you can cite cut, because you're
giving your reader a promise that you could expand it out into a
correctly written proof. For example, suppose that you already have a
proof of the sequent $\phi\vdash\psi$ (which you named ``hocus
pocus''), and that you've begun a new proof where $\phi$ appears on
line $m$. Then on a subsequent line, you can write $\psi$ with a
citation of cut.
\[ \begin{array}{l l l p{3cm}}
\Gamma & (m) & \phi & \\
& \vdots \\
\Gamma & (n) & \psi & cut, hocus pocus \end{array} \] If somebody
then calls you on the cut, you can do the following: take the proof of $\phi\vdash\psi$ and add a line of CP to get a proof of $\vdash\phi\to\psi$. Then instead of citing cut on line $n$, copy in that entire proof, and finish with a step of MP.
\[ \begin{array}{l l >{$}p{1.75cm}<{$} p{2cm}}
\Gamma & (m) & \phi & \\
& \vdots \\
& (n_1) & \phi\to\psi & \\
\Gamma & (n_2) & \psi & $m,n_1$ MPP \end{array} \]
So, using cut with an already proven sequent is just a way of
indicating that you could write a proof.
Many cases of cut involve the special case $n=1$, i.e.\ where you've
already demonstrated that $\phi\vdash\psi$, and you find yourself with
a line like this:
\[ \begin{array}{l l l p{3cm}}
\Gamma & (m) & \phi & \end{array} \]
In this case, cut licenses the following inference:
\[ \begin{array}{l l >{$}p{1cm}<{$} p{3cm}}
\Gamma & (n) & \psi & $m$ cut \end{array} \]
For an example of cut with $n=2$, suppose that you have proved
disjunctive syllogism $P\vee Q,\neg P\vdash Q$, and that you have the
following two lines in a proof:
\[ \begin{array}{r l l p{3cm}}
\Gamma _1 & (m) & P\vee Q \\
\Gamma _2 & (n) & \neg P \end{array} \]
Then cut licenses a subsequent line:
\[ \begin{array}{r l >{$}p{1cm}<{$} p{3cm}}
\Gamma _1,\Gamma _2 & (n') & Q & $m,n$ cut \end{array} \]
The cut rule is also really useful in the case where $n=0$. In that
case, we have already proven a single sequent $\vdash\psi$ that has
no premises. The cut rule then says that on any line of a
subsequent proof, we may write $\psi$ with no dependencies. So, for
example, if we've already proven the law of excluded middle (lem),
$P\vee\neg P$, then any time we're writing a proof, we may insert a
line:
\[ \begin{array}{l c >{$}p{1.5cm}<{$} p{4cm}}
& (n) & P\vee\neg P & cut, LEM \end{array} \]
%% don't forget to extend to SI(s)
This invocation of cut goes beyond substitution, because substitution
only creates an entire new proof. Cut allows you to paste an old
proof in the middle of a new one.
You can, however, use cut together with substitution. For example, if
you've proven excluded middle, then substitution gives you a proof of
$\vdash (P\to Q)\vee \neg (P\to Q)$. Then cut permits you to drop
this sequent into a proof as follows:
\[ \begin{array}{l c >{$}p{4cm}<{$} p{4cm}}
& (n) & (P\to Q)\vee\neg (P\to Q) & cut, LEM \end{array} \]
Technically speaking, this line $n$ should say something like
``substitution + cut''. But substitution is so immediate that it can
typically be used without mention.
Let's look at one more example of the use of cut. We'll take for
granted that you already have proofs of excluded middle
$\vdash P\vee \neg P$, and positive paradox $P\vdash Q\to P$. We will
use these results to prove the sequent $\vdash (P\to Q)\vee (Q\to P)$.
\[ \begin{array}{l l >{$}p{4cm}<{$} p{4cm}}\
& (1) & P\vee \neg P & cut, lem \\
2 & (2) & P & A \\
2 & (3) & Q\to P & 2 cut, pos paradox \\
2 & (4) & (P\to Q)\vee (Q\to P) & 3 $\vee$I \\
5 & (5) & \neg P & A \\
5 & (6) & \neg Q\to \neg P & 5 cut, pos paradox \\
2 & (7) & \neg \neg P & 2 DN \\
2,5 & (8) & \neg\neg Q & 6,7 MTT \\
2,5 & (9) & Q & 8 DN \\
5 & (10) & P\to Q & 2,9 CP \\
5 & (11) & (P\to Q)\vee (Q\to P) & 10 $\vee$I \\
& (12) & (P\to Q)\vee (Q\to P) & 1,2,4,5,11 $\vee$E
\end{array} \]
On line 2 we have the sequent $P\vdash P$. Positive paradox establishes
the sequent $P\vdash Q\to P$. Hence, cut permits us to combine these
two sequents into $P\vdash Q\to P$, which we write on line 3.
We then use positive paradox again to obtain line 6 from line 5.
(Note that if we had permitted ourselves to use negative paradox, then
we could immediately have obtained $P\to Q$ from line 5.)
%% TO DO: powerful to combine substitution with cut
\section{If and Only If}
We have one more meta-rule to cover, viz.\ the replacement rule.
However, we pause to define a symbol that will facilitate our
discussion of replacement.
If you spend any amount of time hanging around mathematicians or
analytic philosophers, you'll pick up the phrase ``if and only if.''
This phrase is meant to express something even stronger than a
conditional; it's meant to express a two-directional conditional, or
\emph{\gls{biconditional}}. For example, if I tell you that
\begin{quote} You will get an A on the exam if and only if you
study \end{quote} then I'm telling you two things. First, ``you
will get an A on the exam if you study,'' which means that studying is
a \emph{sufficient condition} for getting an A on the exam. Second,
``you will get an A on the exam only if you study,'' which means that
studying is a \emph{necessary condition} for getting an A on the exam.
We will use the symbol $\lra$ for the ``if and only if'' connective.
Like a conditional, this connective applies to two sentences; thus, if
$\phi$ and $\psi$ are sentences of propositional logic, then so is
$\phi\lra\psi$. In order for this new connective to be useful, we now
have to specify its inference rules. Fortunately, its meaning is
completely transparent, once we already know how to express ``if \dots
then \dots '', and ``and''. In particular, $\phi\lra\psi$ should be
equivalent to $(\phi\to\psi )\wedge (\psi\to\phi )$. In fact, we will
make this equivalence into a definition of the introduction and
elimination rules.
\bigskip
\begin{tcolorbox}[enhanced,width=11cm,title=biconditional introduction
($\lra$I) and elimination ($\lra$E),attach boxed title to top
left={yshift=-2mm,xshift=4mm},boxed title style={sharp corners}]
\[ \begin{array}{c c c} \begin{array}{c c} \Gamma\:\vdash\: (\phi\to \psi)\wedge (\psi\to \phi) \\
\hline \Gamma\:\vdash\: \phi\lra \psi \end{array} & &
\begin{array}{c c} \Gamma\:\vdash\: \phi\lra \psi \\ \hline
\Gamma\:\vdash\: (\phi\to \psi )\wedge (\psi\to \phi ) \end{array} \end{array} \]
\end{tcolorbox}
\bigskip
To check that these are good inference rules, let's first verify that
``$P$ if and only if $P$'' is tautologous.
\[ \begin{array}{l l >{$}p{3.5cm}<{$} p{3cm}}
1 & (1) & P & A \\
& (2) & P\to P & 1,1 CP \\
& (3) & (P\to P)\wedge (P\to P) & 2,2 $\wedge$I \\
& (4) & P\lra P & 3 $\lra$I \end{array} \]
In technical writing, people often abbreviate ``if and only if'' to
the three letters ``iff''. Another expression that is sometimes used
with the same force is ``just in case''. In particular,
mathematicians often state their definitions by saying something like,
``We'll say that a number $n$ is {\it prime} just in case \dots ''.
By this they mean, a number $n$ is prime if and only if \dots .
Recall that a conditional $P\to Q$ in propositional logic can be
asserted in conditions considerably weaker than those that license
asserting a conditional in some everyday life contexts. In
particular, $Q\vdash P\to Q$, which means that $Q$ itself is a
sufficient condition for $P\to Q$. This result also suggests that
$P\lra Q$ should be assertable in any context where both $P$ and $Q$
are assertable. We verify that fact now.
\[ \begin{array}{l l >{$}p{4cm}<{$} p{4cm}}
1 & (1) & P\wedge Q & A \\
1 & (2) & Q & 1 $\wedge$E \\
1 & (3) & P\to Q & 2 cut, positive paradox \\
1 & (4) & P & 1 $\wedge$E \\
1 & (5) & Q\to P & 4 cut, positive paradox \\
1 & (6) & (P\to Q)\wedge (Q\to P) & 3,5 $\wedge$I \\
1 & (7) & P\lra Q & 6 $\lra$I \end{array} \]
This proof yields the sequent $P\wedge Q\vdash P\lra Q$. A similar
proof (see the exercises) shows that $\neg P\wedge\neg Q\vdash P\lra
Q$. You could then combine these two proofs with a step of
disjunction elimination to prove the sequent:
\[ (P\wedge Q)\vee (\neg P\wedge\neg Q)\: \vdash \: P\lra Q .\]
\begin{exercises} Prove the following sequents. You may invoke cut
with any named sequent that you have already proven (e.g.\ lem,
positive paradox, negative paradox).
\begin{enumerate}
\item $P\lra Q\:\vdash\: Q\lra P$
\item $\vdash\: (Q\to P)\vee (P\to R)$
\item $P\lra Q\:\dashv\vdash\: (P\wedge Q)\vee (\neg P\wedge \neg Q)$
\item $\neg (P\lra P)\:\vdash\: Q\wedge\neg Q$
\item $P\lra Q, Q\lra R\:\vdash\: P\lra R$
\item $\neg (P\lra Q)\:\dashv\vdash\: (P\lra \neg Q)$
\item $\vdash\: (P\lra Q)\vee (P\lra R)\vee (Q\lra R)$
\end{enumerate}
\end{exercises}
%% TO DO: more complicated substitution -- i.e. replacement
\section{Replacement} \label{replacement}
The substitution meta-rule permits only transformations that begin
with atomic sentences, and that propagate through the application of
the logical connectives. The \emph{replacement meta-rule} is more
flexible: it permits replacement of an entire subformula.
The idea behind this meta-rule is simple. Suppose that you have
proven both sequents $\phi\vdash\psi$ and $\psi\vdash\phi$. So, you
know then that $\phi$ and $\psi$ are equivalent, ``for all logical
purposes.'' In particular, whatever inferential relations $\phi$
stands in to any other sentence $\theta$, $\psi$ stands in exactly
those same inferential relations to $\theta$. This suggests that in
any argument, $\psi$ should be able to play the same role as $\phi$.
For example, consider the sequent
\[ R\vee ((Q\to R)\to P) \: \vdash \: R\vee ((\neg Q\vee R)\to P) .\]
This sequent could be proven the long way around by performing
disjunction elimination. After assuming the second disjunct of the
premise, you could then assume $\neg Q\vee R$. Then plug in the proof
of $\neg Q\vee R\vdash Q\to R$, and so on.
Let $\theta$ be the formula $Q\to R$, let $\theta '$ be the formula
$\neg Q\vee R$, and let $\phi$ be the formula $R\vee ((Q\to R)\to P)$.
In other words, $\phi$ is the formula $R\vee (\theta \to P)$, and the
conclusion of the argument is the formula $R\vee (\theta '\to P)$.
After doing many proofs, you'll start to get the feeling that a move
like this can always be done. That is, if one formula $\theta$ occurs
as part of another $\phi$, and if $\theta$ is provably equivalent to
$\theta '$, then you'll always be able to find a proof $\phi\vdash\phi
[\theta '/\theta ]$, where $\phi [\theta '/\theta ]$ is the formula
you get if you replace $\theta$ in $\phi$ with $\theta '$.
But can you be sure that it will always work? The answer is yes, that
you can be sure, but it takes some patient verification to see why.
The key here is simply to check that all of the connectives preserve
inter-derivability of sentences. So, for example, if $\theta$ and
$\theta '$ are inter-derivable, then no matter what sentence $\psi$
is, the conjunction $\theta\wedge\psi$ will be inter-derivable with
$\theta' \wedge\psi$, the conditional $\theta\to\psi$ will be
inter-derivable with $\theta'\to\psi$ and so on. If we apply the same
thought again, it follows that $\chi\vee (\theta\wedge\psi )$ is
inter-derivable with $\chi\vee (\theta '\wedge\psi )$, and so on. In
other words, once you have that $\theta\dashv\vdash\theta '$, then
$\theta$ can be embedded as deeply as you want in some other formula
$\phi$, and it will still be the case that $\phi\dashv\vdash \phi
[\theta '/\theta ]$, where $\phi [\theta '/\theta ]$ is the result of
replacing $\theta$ in $\phi$ with $\theta '$.
Our meta-rule of replacement can be made more convenient for proving
stuff if we remember that $\phi\dashv\vdash\phi [\theta /\theta ']$
implies that if $\Gamma\vdash\phi$ then
$\Gamma\vdash\phi [\theta /\theta ']$. That is, if there's a proof of
$\phi$ from $\Gamma$, then there's also a proof of
$\phi [\theta /\theta ']$.
\bigskip \begin{tcolorbox}[enhanced,width=10cm,title=replacement with
an equivalent (RE),attach boxed title to top
left={yshift=-2mm,xshift=4mm},boxed title style={sharp corners}]
Given a line \mbox{$\Gamma\vdash\phi$ of a proof}, and a sub-formula
$\theta$ of $\phi$, if $\theta$ is equivalent to $\theta '$, then
you may infer a sub{-}sequent line
$\Gamma\vdash\phi [\theta '/\theta]$, where $\theta$ has been
replaced by $\theta '$. Schematically: \[ \begin{array}{c c}
\vdash\theta\lra\theta ' \qquad \Gamma\vdash\phi \\ \hline
\Gamma\vdash \phi [\theta '/\theta] \end{array} \]
\end{tcolorbox}
\bigskip The replacement meta-rule can be used with any equivalences
that have already been proven. If you keep in mind some key
equivalences (see page \pageref{equivs}), then it can really speed up
proofs. Consider, for example, the following alternative proof of
Peirce's law.
% \[ \begin{array}{l l l p{4cm}}
% 1 & (1) & (P\to Q)\to P & A \\
% 2 & (2) & \neg P & A \\
% 1,2 & (3) & \neg (P\to Q) & 1,2 MTT \\
% 1,2 & (4) & P\wedge\neg Q & 3 mat cond \\
% 1,2 & (5) & P & 4 $\wedge$E \\
% 1,2 & (6) & P\wedge \neg P & 5,2 $\wedge$I \\
% 1 & (7) & \neg \neg P & 2,6 RAA \\
% 1 & (8) & P & 7 DN \end{array} \]
\[ \begin{array}{l l >{$}p{3cm}<{$} p{4cm}}
1 & (1) & (P\to Q)\to P & A \\
1 & (2) & \neg (P\to Q)\vee P & 1 RE, mat cond \\
1 & (3) & (P\wedge \neg Q)\vee P & 2 RE, mat cond \\
4 & (4) & P\wedge \neg Q & A \\
4 & (5) & P & 4 $\wedge$E \\
6 & (6) & P & A \\
1 & (7) & P & 3,4,5,6,6 $\vee$E \end{array} \]
On line 2, we used replacement on the entire line with the equivalence
$\phi\to\psi \dashv\vdash \neg\phi\vee \psi$. (When replacement is applied
to an entire line, we could also have used cut.) On line 3, we used
replacement on the first disjunct with the equivalence $\neg
(\phi\to\psi )\dashv\vdash \phi\wedge\neg\psi$.
The replacement meta-rule can be especially helpful if you need to
convert a sentence $\phi$ into an inter-derivable sentence $\phi '$
that has some specific form. For example, one particularly nice kind
of sentence is one where all negation signs apply only to atomic
sentences; all conjunction symbols apply only to atomic or negated
atomic sentences; and where there are no conditional or biconditional
connectives. (Such sentences are said to be in \emph{disjunctive
normal form}, and we will investigate them further in Chapter
\ref{truth}.) For example, the following sentence has this form:
\[ (P\wedge Q)\vee (P\wedge\neg Q)\vee (\neg P\wedge Q)\vee (\neg
P\wedge\neg Q) .\] We won't provide a detailed recipe here for
finding equivalent disjunctive normal form sentences, but instead
we'll just work a couple of examples.
First, we write a proof of the sequent
\[ (P\to Q)\vee (Q\to P)\:\vdash\: (P\vee\neg P)\vee (Q\vee\neg Q) .\]
\[ \begin{array}{l l >{$}p{4.5cm}<{$} p{3cm}}
1 & (1) & (P\to Q)\vee (Q\to P) & A \\
1 & (2) & (\neg P\vee Q)\vee (\neg Q\vee P) & 1 RE \\
1 & (3) & \neg P\vee (Q\vee (\neg Q\vee P)) & 2 RE \\
1 & (4) & \neg P\vee ((Q\vee \neg Q)\vee P) & 3 RE \\
1 & (5) & \neg P\vee (P\vee (Q\vee\neg Q)) & 4 RE \\
1 & (6) & (\neg P\vee P)\vee (Q\vee \neg Q) & 5 RE \\
1 & (7) & (P\vee\neg P)\vee (Q\vee \neg Q) & 6 RE \end{array} \]
Since the conclusion here is a tautology, it's not surprising that it
can be derived from the premise. (It can, in fact, be derived from
any premise.) What's interesting is that each step of this proof
uses RE, and so the derivation is reversible --- hence, the premise
and conclusion are logically equivalent.
\begin{exercise} In the proof above, identify each equivalence that
has been used. \end{exercise}
Now we convert $P\lra Q$ to $(P\wedge Q)\vee (\neg P\wedge\neg Q)$
using a string of equivalences.
\[ \begin{array}{r c l l}
P\lra Q & \dashv\vdash & (P\to Q)\wedge (Q\to P) & \\
& \dashv\vdash & (\neg P\vee Q)\wedge (\neg Q\vee P) & \\
& \dashv\vdash & ((\neg P\vee Q)\wedge\neg Q)\vee ((\neg P\vee
Q)\wedge P) \\
& \dashv\vdash & ((\neg P\wedge\neg Q)\vee (Q\wedge\neg Q))\vee
((\neg P\wedge P)\vee (Q\wedge P)) \\
& \dashv\vdash & (\neg P\wedge\neg Q)\vee (Q\wedge P) .
\end{array} \]
In the final line, we used the fact that for any contradiction $\bot$, and
for any sentence $\phi$, we have $\phi\vee\bot\dashv\vdash\phi\dashv\vdash\bot\vee\phi$. In this sense, a
contradiction acts like a zero (i.e.\ an additive identity) for the $\vee$ operation.
\begin{exercises} Use replacement-style reasoning to convert the
following sentences to disjunctive normal form. You might wish to
consult the equivalences on page \pageref{equivs}.
\begin{enumerate}
\item $(P\to Q)\vee (Q\to R)$
\item $(P\lra Q)\vee (P\lra R)\vee (Q\lra R)$
\end{enumerate}
\end{exercises}
% Indeed, if a
% sentence is longer than just a single symbol, then the last
% construction step must have been to apply some connective $\otimes$ to
% two other sentences $\phi$ and $\psi$.
%% TO DO: resume of rules (including dependencies)
%% TO DO: sequent introduction & theorem introduction
% the picture can just be a bit misleading because it might occur that $m_i$ occurs in $\Delta _i$; but our notation doesn't indicate that in that case, $m_i$ should be removed from $\Delta _i$ in the final tabulation on line $n$.
% Recall, however, that
% we need to keep track of the context in which the premise $P_1\vee P_2$
% is obtained, as well as the contexts in which the conditionals $P_1\to
% Q$ and $P_2\to Q$ are obtained. In this particular case, we
% could use $\Gamma$ for information obtained from Angelina, and
% $\Delta$ for information obtained from club rules. Then the
% inference could be represented as:
% \[ \begin{array}{c} \Gamma \:\vdash \:P_1\vee P_2 \qquad \Delta
% \:\vdash\:P_1\to Q \qquad \Delta \:\vdash\:P_2\to Q \\
% \hline \Gamma ,\Delta \:\vdash\: Q \end{array} \] Here the
% conclusion $Q$ depends on both the information from Angelina ($\Gamma$) and the club rules ($\Delta$). Let's represent the argument again, this time approximating a linear format:
% \[ \begin{array}{l l >{$}p{2cm}<{$} p{1.5cm}}
% \Gamma & (1) & P_1\vee P_2 & A \\
% \Delta & (2) & P_2\to Q & A \\
% \Delta & (3) & P_2\to Q & A \\
% \Gamma ,\Delta & (4) & Q & 1,2,3 $\vee$E \end{array} \]
% In the final line, we have explicitly stated that the inference is
% permitted by our new rule: disjunction elimination ($\vee$E).
% However, the official disjunction elim rule will need to be
% cast in a slightly more general form. First of all, we do {\it not}
% want to require that the second instance of the conclusion (line $3$
% in the proof above) depend on the {\it same} things as the first
% instance of the conclusion (line $2$ above). Hence, in general, we
% should allow something like this:
% \[ \begin{array}{l l >{$}p{2cm}<{$} p{1.5cm}}
% \Gamma & (1) & P_1\vee P_2 & A \\
% \Delta _1 & (2) & P_1\to Q & A \\
% \Delta _2 & (3) & P_2\to Q & A \\
% \Gamma ,\Delta _1 ,\Delta _2 & (4) & Q & 1,2,3 $\vee$E \end{array} \]
% Second, we want in general for our introduction and elimination rules
% for a connective (say $\vee$) not to refer to some other connective
% (say $\to$). Thus, it would be best if we formulated the Disjunction
% Elimination rule without requiring that the second and third premises
% be conditional statements. In this case, instead of using $\Delta
% \vdash P_1\to Q$ as the second premise, we could use $\Delta ,P_1\vdash
% Q$, which --- you will recall --- means that, ``there is a proof of
% $Q$ from $\Delta$ and $P_1$.'' Thus, in fact, we should think of the
% Disjunction Elimination rule as taking three {\it proofs}
% as input, and giving a new proof as output. The input proofs are:
% \begin{enumerate}
% \item $\Gamma\vdash P_1\vee P_2\:$ (a proof of a disjunctive
% statement)
% \item $\Delta _1,P_1\:\vdash Q\:$ (a proof of a conclusion $Q$ from the
% first disjunct $P_2$ and possibly some auxiliary information
% $\Delta _1$)
% \item $\Delta _2,P_2\:\vdash Q\:$ (a proof of the same conclusion $Q$
% from the second disjunct $P_2$ and possibly some other auxiliary
% information $\Delta _2$)
% \end{enumerate}
% The disjunction elimination rule states that: these three input
% proofs may be converted to the following output proof:
% \[ \Gamma ,\Delta _1 ,\Delta _2 \: \vdash \: Q \] Just as conditional
% proof converts a proof of $Q$ from $P$ into a proof of $P\to Q$,
% disjunction elimination converts proofs of $Q$ from $P_1$ and $P_2$
% into a proof of $Q$ from $P_1\vee P_2$. The official statement of
% the rule is as follows:
% Suppose that we ask you to prove the sequent:
% \[ \:\vdash (R\to S)\vee (S\to R) \]
% It would not be unreasonable to try to prove this sequent by means of
% reductio ad absurdum. To this end, you would first assume the
% negation of the conclusion:
% \[ \begin{array}{l l l p{1.5cm}}
% 1 & (1) & \neg ((R\to S)\vee (S\to R)) & A \end{array} \]
% You might then remember that you previously proved DeMorgan's law
% \[ \neg (P\vee Q)\:\vdash\: \neg P\wedge\neg Q \]
% And you would be right to think that you could repeat this proof using
% $R\to S$ in place of $P$, and $S\to R$ in place of $Q$. The result
% then would be a line that looks like this:
% \[ \begin{array}{l l l l} 1 & (n) & \neg (R\to S)\wedge \neg (S\to R)
% & \end{array} \] You might then remember proving
% $\neg (P\to Q)\vdash P\wedge \neg Q$, and if you make the proper
% substitutions, then from line $n$ you could first derive $R$ from
% $\neg (R\to S)$, and then $\neg R$ from $\neg (S\to R)$. You will
% then have shown that the assumption on line 1 leads to both $R$ and
% $\neg R$; hence you can apply RAA to obtain $\neg \neg ((R\to S)\vee
% (S\to R))$.
%% truth tables -- but without explaining why they work
%%% Local Variables:
%%% mode: latex
%%% TeX-master: "main"
%%% End: